Oromandibular-limb Hypogenesis Syndrome Type II C: A Rare Case - Renita Lorina Castelino; Shishir Ram Shetty; Subhas Babu G; Kumuda Arvind Rao H T (Tabriz University of Medical Sciences, 2010)
The oromandibular-limb hypogenesis syndrome comprises a group of anomalies which simultaneously affect the mandible, tongue, and maxilla with or without reductive limb anomalies. It is characterized by failure of development of the intraoral region and distal extremities. Multiple and variable deformities of the mandible, maxilla and tongue may occur in combination with a variety of limb defects. The wide range of presentation and combination of anomalies make classification difficult. They usually feature primarily in sporadic case reports because of their low incidence. The genetic origin of this syndrome is uncertain. It is congenital and there seems to be no sex predilection. The key radiographic features are retruded mandible, impacted teeth and malformed phalanges. When compared to available literature, frequently reported features like hypodontia, hypoglossia, microstomia, protruded maxilla and limb anomalies were present in our case. The case presented here is one of the rarest subtypes of this rare syndrome.